Metriorhynchidae (Crocodylomorpha: Thalattosuchia) from upper jurassic–lower cretaceous of Neuquén basin (Argentina), with comments on the natural casts of the brain - Herrera, Laura Yanina (2015)
Metriorhynchidae was the only Crocodylomorpha with a pelagic marine lifestyle. Related to this lifestyle, its peculiar body plan al- lows clearly differentiate them from others Crocodylomorpha. The fossil record of metriorhynchids from Tithonian–Berriasian levels of the Vaca Muerta Formation (Neuquén Basin, Argentina) is outstanding, in terms of quantitative and qualitative record. Its taxonomical diversity is composed by four taxa: Cricosaurus araucanensis, Cricosaurus lithographicus, Dakosaurus andiniensis, and Purranisaurus potens. This fossil record is also characterized by the tridimensional preservation of the materials and by the preservation of numerous natural endocasts of the skull cavities. Here, I made a description of the natural endocasts of the brain of Cricosaurus araucanensis together with a synthesis of the advances in the knowledge of these four taxa that were performed during the last years. The information that provides the endocasts, to- gether with the quantity of endocasts, make of the Patagonian fossil record of metriorhynchids a key to the exploration and reconstruction of soft anatomy of these crocodylomorphs, and for the understanding of the physiological changes that accompanied the structural changes of the skeleton. Understanding these changes will allow defining the key innovations that allowed to the metriorhynchids conquer the pelagic environment, unparalleled among archosaurs.